The designer's guide to the Cortex-M processor family - Martin, Trevor (Newnes is an imprint of Elsevier, 2016)
Annotation
Includes index
Keywords: COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Microprocessors; RISC microprocessors; C -- Programmiersprache; Mikroprozessor; ARM -- Computerarchitektur; ARM Cortex-M; RISC